The Full Has Never Been Told: Theology and the Encounter with Globalization - Duncanson-Hales, Christopher (Université Saint-Paul / Saint Paul University, 2011)
My thesis, "The Full has Never been Told: Theology and the Encounter with Globalization," is an investigation of the encounter between religion and globalization. Rastafari reggae performer Buju Banton's song, Untold Story (Banton, 2002) recounts a variety of injustices and sufferings inflicted on 'low-budget people', each concluding with the refrain, "I could go on and on, the full has never been told." The full has never been told is the hermeneutic orientation of my research that encapsulates the suffering of the wretched of the earth as they encountered the oppressive forces of globalization and the hope that inevitably emerges from this encounter. My research begins with an understanding of globalization not as a clash of civilizations, but as a clash of symbols and metaphors. An important insight I have investigated is the theoretical significance of the 'deterritorialization' of symbols as a primary, long run driving force of economic, political, and social globalization and globalization's encounter in the developing world as a boundary situation. The Caribbean's experience of transatlantic slavery, colonization/decolonization, the in-migration of indentured labour, and the continued out-migration of West Indian's through-out the globe represents the first clash with the boundary situation of globalization. Paul Ricoeur identifies boundary situations as encounters with "war, suffering, guilt, death and so which the individual or community experience as a fundamental existential crisis." In the Caribbean, these boundary situations require solutions beyond purely political, economic or technical means. They demand, as Ricoeur notes, "we ask ourselves the ultimate question concerning our origins and ends: Where do we come from? Where are we going? In this way we become aware of our basic capacities and reason for surviving, for being and continuing to be what we are." These questions and contradictions are at the core of theology's encounter with globalization. This project employs an interdisciplinary methodology using Paul Ricoeur's phenomenological hermeneutic of the productive imagination, Niklas Luhmann and Peter Beyer's social theory of the communicative characteristic of global society and Rastafari's interpretation of word, sound and power in their encounter with globalization. The theoretical framework of my project follows Paul Ricoeur's hermeneutic arc. The first moment of the arc, pre-understanding, introduces the historical framework of globalization and religion. In the second moment of the arc, configuration, this framework is configured with Ricoeur's presentation of the productive imagination to present a hermeneutic model for understanding and explaining the symbolic and mythic encounter of globalization. In the final moment of the arc, application, the Rastafari hermeneutic of word, sound and power emerging from the Rastafari experience of globalization shows itself as an exemplar of an ontology of hope that has passed through despair.
Keywords: Globalization; Comparative Theology; Theology and the Social Sciences; Niklas Luhmann; Paul Ricoeur; Social Systems; Productive Imagination; Rastafari; Caribbean Theology; Post-colonial Theology; Heremeneutics; Phenomenology; Radical Constructivism; Ontology of Hope